2004
DOI: 10.1074/jbc.m404232200
|View full text |Cite
|
Sign up to set email alerts
|

Purine Salvage Pathways in the Apicomplexan Parasite Toxoplasma gondii

Abstract: We have exploited a variety of molecular genetic, biochemical, and genomic techniques to investigate the roles of purine salvage enzymes in the protozoan parasite Toxoplasma gondii. The ability to generate defined genetic knockouts and target transgenes to specific loci demonstrates that T. gondii uses two (and only two) pathways for purine salvage, defined by the enzymes hypoxanthine-xanthine-guanine phosphoribosyltransferase (HXGPRT) and adenosine kinase (AK). Both HXGPRT and AK are single-copy genes, and ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 51 publications
4
104
0
1
Order By: Relevance
“…No additional candidate orthologues were found. These results have been independently confirmed by other groups (13,15). In addition, no potential homologues were found for the Bacillus subtilis proteins expressed by the mtnK, mtnY, mtnW, mtnX, mtnZ, and mtnV genes that are proposed to constitute the methionine salvage pathway (16).…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…No additional candidate orthologues were found. These results have been independently confirmed by other groups (13,15). In addition, no potential homologues were found for the Bacillus subtilis proteins expressed by the mtnK, mtnY, mtnW, mtnX, mtnZ, and mtnV genes that are proposed to constitute the methionine salvage pathway (16).…”
Section: Methodssupporting
confidence: 74%
“…We were also unable to find orthologues of other potential purine salvage enzymes that have been reported in other organisms but not in the Plasmodium species. Other groups have independently come to similar conclusions (13,15).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…T. gondii is an auxotroph for tryptophan [19][20][21], arginine [22,23], polyamines [24], purines [25,26], cholesterol [27,28], iron [23,29], and other essential nutrients [30]. Although parasites surrounded by the PVM are protected against the acidification from the fusion of endocytic vesicle, this non-fusion state deprives parasites of an abundant source of nutrients from the host's endocytic and exocytic system.…”
Section: Subversion Of Host Organelles Cytoskeleton and Lysosomesmentioning
confidence: 99%
“…First, T. gondii is a purine auxotroph and depends on the salvage pathways for its purine requirements, and the salvage of adenosine is the major source of purines in T. gondii [14,15]. Specifically, the activity of adenosine kinase (EC.2.7.1.20), the enzyme responsible for the salvage of adenosine in this parasite, is 10-fold higher than those of other enzymes in the purine salvage pathways, and hence contributes more significantly to the salvage of purines in T. gondii than any other enzyme of the purine salvage pathways [12][13][14][15][16]. Secondly, structure-activity relationships [17,18], comparative enzymatic [18][19][20], metabolic [19][20][21], molecular [22], and X-ray structural studies [23][24][25] have demonstrated that there are sufficient differences between the active sites and substrate specificities of human and T. gondii adenosine kinases that can be exploited to design specific "subversive substrates" for the T. gondii enzyme [12,13].…”
Section: Introductionmentioning
confidence: 99%